Quadruplex Nucleic Acids - Neidle, Stephen ;Ed. Balasubramanian, Shankar; Ed (Royal Society of Chemistry, 2006)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity.